2018
DOI: 10.5607/en.2018.27.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Gamma Knife Radiosurgery as Initial Treatment for Large Skull Base Meningioma

Abstract: We present our experience on the hypofractionated Gamma Knife radiosurgery (FGKS) for large skull base meningioma as an initial treatment. We retrospectively reviewed 23 patients with large skull base meningioma ≥10 cm3 who underwent FGKS as the initial treatment option. The mean volume of tumors prior to radiosurgery was 21.2±15.63 cm3 (range, 10.09~71.42). The median total margin dose and marginal dose per fraction were 18 Gy (range, 15~20) and 6 Gy (range, 5~6), respectively. Patients underwent three or fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 66 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…For the predictors of tumor recurrence or progression, some studies revealed that increasing tumor volume was an independent predictor, which was also proved in our study. 10,16,29 In this study, many patients with intracranial meningiomas had low subjective acceptance of craniotomy; even though there were significant mass effect or neurological symptoms or signs, they preferred GKRS instead of craniotomy, which resulted in a high rate of large tumor (≥ 10 cm 3 ) in proportion at the time of GKRS, and reduced the treatment effect of GKRS in the cohort. In addition, a GKRS dose-plan defect may also influence local tumor control.…”
Section: Discussionmentioning
confidence: 77%
“…For the predictors of tumor recurrence or progression, some studies revealed that increasing tumor volume was an independent predictor, which was also proved in our study. 10,16,29 In this study, many patients with intracranial meningiomas had low subjective acceptance of craniotomy; even though there were significant mass effect or neurological symptoms or signs, they preferred GKRS instead of craniotomy, which resulted in a high rate of large tumor (≥ 10 cm 3 ) in proportion at the time of GKRS, and reduced the treatment effect of GKRS in the cohort. In addition, a GKRS dose-plan defect may also influence local tumor control.…”
Section: Discussionmentioning
confidence: 77%
“…More recently, the GK which has traditionally been a single-fraction device (outside of staged treatments which are 1 month apart), has been increasingly used in a hypofractionated manner. 12,13 A group from South Korea reported on outcomes in 70 patients with tumors >10 cm 3 . 12 Of those patients, 60% were treated in a single fraction to 12 Gy, and the remaining patients were treated in two to four fractions, total doses ranging from 15 to 18 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Available data on this approach are limited compared to SRS; however, results appear to be promising in terms of safety and efficacy. 1113 Over the last decade, patients diagnosed with meningioma and treated with radiotherapy have typically been managed with this hypofractionated approach at our institution. Herein, we present the results of our experience using SRT in the management of meningioma.…”
Section: Background and Purposementioning
confidence: 99%
“…Park et al found fractionated radiosurgery using the Gamma Knife Perfexion for large (> 10 cm 3 ) SBMs to be safe and effective, with only 17% of patients experiencing new-onset cranial neuropathy. 36 The median tumor volume in our series was 7.62 cm 3 (range 4.57-13.07 cm 3 ) with an overall progression-free survival of 82.5% at 1 year. Four of these patients were followed up to 40 months and had a median reduction in volume of 30% (−39.3 to −12.3).…”
Section: Fgkrs In Large Tumorsmentioning
confidence: 58%
“…32 To the best of our knowledge, there are only 4 institutional experiences previously published that describe this technique. 10,18,32,36 We present a retrospective review of 25 cases of SBM treated with fGKRS: 6 patients treated with the Extend system and 19 patients with the Icon system. This article presents the unique experience of using fGKRS in cases of SBM and represents the largest experience to date of using the Icon system.…”
mentioning
confidence: 99%